Anode for fluoride ion secondary battery and fluoride ion secondary battery including the same

A composite of Li3AlF6 and AlF3 in the negative electrode of fluoride ion secondary batteries addresses the low capacity issue by enhancing ionic conductivity and active material concentration, resulting in increased battery capacity and efficiency.

JP7604248B2Active Publication Date: 2024-12-23HONDA MOTOR CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021010581
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-26
Publication Date
2024-12-23
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

Conventional fluoride ion secondary batteries face challenges with low battery capacity due to the insulating properties of aluminum fluoride, which hinders electrochemical reactions and limits the concentration of the negative electrode active material.

Method used

A composite negative electrode active material composed of Li3AlF6 and AlF3 is developed, with a molar ratio of 0.1 to 2 and a content of 25% by mass or less, which promotes ionic conductivity and defluorination, allowing for higher active material concentration and increased battery capacity.

Benefits of technology

The composite material achieves higher battery capacity, improved ionic conductivity, and enhanced active material utilization rate, with coulombic efficiency reaching up to 80% compared to conventional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604248000001
    Figure 0007604248000001
  • Figure 0007604248000002
    Figure 0007604248000002
  • Figure 0007604248000003
    Figure 0007604248000003
Patent Text Reader

Abstract

To provide a fluoride ion secondary battery larger, in battery capacity, than conventional ones.SOLUTION: A negative electrode for a fluoride ion secondary battery contains a composite of Li3AlF6 and AlF3 as a negative electrode active material. The mole ratio of AlF3 to Li3AlF6 in the composite of Li3AlF6 and AlF3 is preferably 0.1 to 2. The content of the composite of Li3AlF6 and AlF3 in the negative electrode for a fluoride ion secondary battery is preferably 25 mass% or less. The composite of Li3AlF6 and AlF3 is preferably amorphous.SELECTED DRAWING: Figure 7
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for a fluoride ion secondary battery and a fluoride ion secondary battery including the same. [Background technology]

[0002] Conventionally, fluoride ion secondary batteries using fluoride ions as a carrier have been proposed (for example, see Patent Documents 1 to 6). Fluoride ion secondary batteries are expected to have battery characteristics that exceed those of lithium ion secondary batteries, and various studies have been conducted in recent years.

[0003] For example, aluminum-based materials are candidates for the negative electrode active material of fluoride ion secondary batteries. Among them, the use of aluminum fluoride has been studied, but aluminum fluoride has an issue in that it is difficult for electrochemical reactions to occur because it has electrical insulation properties. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-87403 A [Patent Document 2] JP 2017-50113 A [Patent Document 3] JP 2019-29206 A [Patent Document 4] JP 2018-206755 A [Patent Document 5] JP 2018-198130 A [Patent Document 6] JP 2018-92863 A Summary of the Invention [Problem to be solved by the invention]

[0005] Therefore, the applicant has developed a modified AlF3 As a negative electrode active material, fluoride ion secondary batteries using aluminum fluoride have been developed, but there is currently a demand for further improvements in battery characteristics. In particular, modified AlF 3 However, since the ionic conductivity of such a negative electrode active material is not good, it is not possible to increase the concentration of the negative electrode active material in the negative electrode, and it is not easy to increase the battery capacity.

[0006] The present invention has been made in view of the above, and has an object to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries. [Means for solving the problem]

[0007] (1) The present invention relates to a negative electrode for a fluoride ion secondary battery, comprising a negative electrode active material, the negative electrode active material being Li 3 AlF 6 and AlF 3 The present invention provides a negative electrode for a fluoride ion secondary battery, comprising a composite of

[0008] (2) In the negative electrode for a fluoride ion secondary battery according to (1), 3 AlF 6 and AlF 3 Li in the complex 3 AlF 6 AlF 3 The molar ratio may be from 0.1 to 2.

[0009] (3) In the negative electrode for a fluoride ion secondary battery according to (1) or (2), the Li 3 AlF 6 and AlF 3 The content of the complex may be 25% by mass or less.

[0010] (4) In the negative electrode for a fluoride ion secondary battery according to any one of (1) to (3), the Li 3 AlF 6 and AlF 3 The complex may be amorphous.

[0011] (5) The present invention also provides a fluoride ion secondary battery comprising a negative electrode for a fluoride ion secondary battery according to any one of (1) to (4). Effect of the Invention

[0012] According to the present invention, it is possible to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a diagram showing a method for synthesizing a composite of Li3AlF6 and AlF3 as a negative electrode active material according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an X-ray diffraction spectrum of a composite of Li3AlF6 and AlF3 as a negative electrode active material according to the embodiment. [Diagram 3] FIG. 1 is a diagram showing the properties of a composite of Li3AlF6 and AlF3 and conventional modified AlF3. [Figure 4] 1A to 1C are diagrams illustrating an example of a method for producing a negative electrode for a fluoride ion secondary battery according to an embodiment of the present invention. [Diagram 5] FIG. 1 is a diagram showing an example of a conventional method for producing a negative electrode for a fluoride ion secondary battery. [Figure 6] FIG. 2 is an NMR spectrum diagram of a composite of Li3AlF6 and AlF3 as a negative electrode active material according to the embodiment. [Figure 7] 1 is a diagram showing charge / discharge curves of negative electrode half-cells for fluoride ion secondary batteries according to Examples 1 and 2, Reference Example 1, and Comparative Example 1. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.

[0015] [Negative electrodes for fluoride ion secondary batteries] The negative electrode for a fluoride ion secondary battery according to this embodiment contains Li as a negative electrode active material. 3AlF 6 and AlF 3 Contains complexes of Li 3 AlF 6 and AlF 3 A negative electrode for a fluoride ion secondary battery containing a complex of the above has not been found so far, and the negative electrode for a fluoride ion secondary battery according to this embodiment contains Li 3 AlF 6 and AlF 3 It is characterized in that it contains a complex of

[0016] Li 3 AlF 6 and AlF 3 The composite functions as a negative electrode active material during charging and discharging. 3 AlF 6 and AlF 3 When charged, the complex becomes a fluoride ion, F - During discharge, fluoride ions F - Absorbs.

[0017] Li according to this embodiment 3 AlF 6 and AlF 3 The complex is Li 3 AlF 6 and AlF 3 In this composite, Li with ionic conductivity is 3 AlF 6 However, it functions as a fluorine source and also acts as a defluorinator for AlF, which is normally difficult to defluorinate. 3 It acts as a catalyst to promote the defluorination of

[0018] Li 3 AlF 6 and AlF 3 Li in the complex 3 AlF 6 AlF 3 The molar ratio of Li is preferably 0.1 to 2. 3 AlF 6 :AlF 3 It is preferable that the complex is formed by coexisting in a molar ratio of Li = 1 mol:0.1 mol to 1 mol:2 mol.3 AlF 6 AlF per mole 3 If the molar ratio of is less than 0.1 mol, the above-mentioned AlF 3 On the other hand, the promotion of defluorination of Li 3 AlF 6 AlF per mole 3 When the molar ratio exceeds 2, insulating AlF 3 If a large amount of is present, the ionic conductivity decreases and the battery will no longer function.

[0019] Next, Li 3 AlF 6 and AlF 3 The method for synthesizing the complex will be described with reference to FIG. FIG. 1 is a graph showing a negative electrode active material according to the present embodiment. 3 AlF 6 and AlF 3 FIG. 1 is a diagram showing a method for synthesizing the Li complex according to the present embodiment. 3 AlF 6 and AlF 3 The complex is LiF and AlF 3 The mixture is mixed in a predetermined ratio and sintered. The mixture is then subjected to a ball milling process at 400 rpm for 15 minutes for 40 cycles, and then sintered at 900°C for 3 hours. After sintering, the mixture is pulverized to obtain Li as the negative electrode active material according to the present embodiment. 3 AlF 6 and AlF 3 A complex of the formula:

[0020] Here, the temperature of the sintering process is preferably within a range of 850° C. to 900° C. Since the melting point of the raw material LiF is 850° C., if the temperature of the sintering process is within this range, the molten LiF and AlF 3 If the sintering temperature exceeds 900°C, the weight loss after sintering starts to increase and the raw materials evaporate, which is not preferable.

[0021] The sintering time is preferably within a range of 2 to 3 hours when the sintering temperature is 850° C. to 900° C. If the sintering time is less than 2 hours, LiF and AlF 3 If the sintering time exceeds 3 hours, the raw materials are evaporated, resulting in a poor yield.

[0022] The pulverization after the sintering process may be performed by, for example, crushing in an agate mortar, and the particles after crushing are microparticles. These microparticles are further crushed by a ball mill crushing process during the production of the negative electrode composite powder, which will be described later.

[0023] Here, LiF and AlF 3 The mixing ratio of LiF:AlF is 3 It is preferable that the ratio of Li to Li is within the range of 1:1 to 3:1.1. By mixing and sintering the two within this range, the Li 3 AlF 6 AlF 3 A composite with a molar ratio of AlF of 0.1 to 2 is obtained. 3 When the amount of LiF is less than 1 mole per mole of AlF, the insulating AlF 3 A large amount of AlF remains, which reduces the ionic conductivity. 3 If the amount of LiF exceeds 3 moles per 1.1 moles, a large amount of insulating LiF remains, resulting in a decrease in ionic conductivity.

[0024] In addition, LiF:AlF 3 When mixed at a molar ratio of 3:1 and sintered, Li 3 AlF 6 This Li 3 AlF 6 However, in this case, there is a concern that the use of lithium element may increase costs, and according to the present embodiment, the amount of LiF used can be reduced, which is preferable from the viewpoint of costs.

[0025] FIG. 2 shows a Li 3AlF 6 and AlF 3 In FIG. 2, from the top to bottom, the composite product synthesized according to the synthesis method in FIG. 1, AlF 3 (theoretical calculation value), LiF (theoretical calculation value), Li 3 AlF 6 The X-ray diffraction spectra of the synthesized compounds are shown in the top row as LiF and AlF. 3 The molar ratio of LiF:AlF 3 = 3:1, LiF and AlF 3 The molar ratio of LiF:AlF 3 = 2:1, LiF and AlF 3 The molar ratio of LiF:AlF 3 This indicates a synthetic product synthesized at a ratio of 1:1.

[0026] As shown in Figure 2, among the products synthesized according to the synthesis method in Figure 1, LiF and AlF 3 The molar ratio of LiF:AlF 3 = 2:1, and LiF and AlF 3 The molar ratio of LiF:AlF 3 In the X-ray diffraction spectrum of the product synthesized at a ratio of 1:1, the peaks derived from the raw material LiF disappeared, while the peaks derived from Li 3 AlF 6 Peaks derived from AlF 3 In contrast, peaks due to LiF and AlF 3 The molar ratio of LiF:AlF 3 In the synthesis product synthesized at a ratio of LiF = 3:1, the peaks derived from the raw material LiF and AlF 3 All peaks derived from Li disappeared. 3 AlF 6 Only the peaks due to LiF and AlF are observed. 3 The mixture molar ratio of LiF:AlF 3 By setting the ratio within the range of 1:1 to 3:1.1, the Li 3 AlF 6 and AlF 3It is confirmed that a complex of the above formula is obtained.

[0027] The negative electrode active material according to the present embodiment is preferably amorphous. 3 AlF 6 and AlF 3 The composite is crystalline as is clear from the X-ray diffraction spectrum of FIG. 2, but becomes amorphous during the manufacturing process of the negative electrode for a fluoride ion secondary battery according to the present embodiment described later. This is because the Li 3 AlF 6 and AlF 3 It is believed that the composite has an unstable crystal structure, and that the crystal structure is destroyed and made amorphous by the ball mill crushing process in the manufacturing process described later. 3 AlF 6 It is believed that this allows the material to bond closely with the solid electrolyte and conductive additive, making it possible to form a high-quality interface.

[0028] Li in the negative electrode for the fluoride ion secondary battery according to this embodiment 3 AlF 6 and AlF 3 The content of the composite is preferably 25 mass % or less. As described above, the present applicant previously discovered modified AlF 3 In the case of Li 2 O 3 , the upper limit of the content in the negative electrode for a fluoride ion secondary battery is 12.5 mass %. 3 AlF 6 and AlF 3 The upper limit of the content of the composite in the negative electrode for a fluoride ion secondary battery can be increased to 25 mass %, which allows the battery capacity to be significantly increased compared to the conventional case.

[0029] Li according to this embodiment 3 AlF 6 and AlF 3The average particle size of the composite is preferably on the order of micrometers. 3 In contrast, in this embodiment, the negative electrode active material is Li 3 AlF 6 and AlF 3 By constructing the composite with microparticles with an average particle size on the order of micrometers, it is possible to achieve a higher density. This is because it is possible to obtain a higher ionic conductivity and increase the battery capacity. 3 AlF 6 and AlF 3 Complex of In order to obtain this, the raw material must be AlF, which is composed of microparticles with an average particle size on the order of micrometers. 3 and LiF. 3 Unlike the Li 3 AlF 6 and AlF 3 The composite is subjected to a sintering process, which also increases the grain size.

[0030] Here, Figure 3 shows Li 3 AlF 6 and AlF 3 and modified AlF, which is made by doping conventional aluminum fluoride with lithium metal. 3 1 is a graph showing the characteristics of Li 3 AlF 6 and AlF 3 As a complex of LiF and AlF 3 Molar ratio of LiF:AlF 3 In addition to the products synthesized in a 2:1 ratio and a 1:1 ratio, LiF and AlF 3 Molar ratio of LiF:AlF 3 =3:1 (i.e., Li 3 AlF 6 ) and conventional modified AlF 3The figures show the actual measured density values ​​for both materials, as well as their ionic conductivity at 140°C, which is the temperature at which a fluoride ion secondary battery is operating.

[0031] As shown in Figure 3, Li 3 AlF 6 and AlF 3 The complex is Li 3 AlF 6 Similarly, conventional modified AlF 3 It can be seen that the density can be increased more than that of Li, and the ionic conductivity of the Li is also high. 3 AlF 6 and AlF 3 The composite is modified AlF 3 Since the concentration can be increased compared to Li, the battery capacity can be increased as described above. 3 AlF 6 and AlF 3 In the composite of the above, even if the concentration is increased, an increase in the volume can be suppressed. Therefore, the content of the solid electrolyte made of a fluoride ion-conductive fluoride described later and the content of the conductive assistant can be increased, resulting in a higher ion conductivity.

[0032] The negative electrode for a fluoride ion secondary battery according to this embodiment contains Li as the negative electrode active material. 3 AlF 6 and AlF 3 In addition to the complex, it is preferable that the composite further contains a solid electrolyte made of a fluoride ion-conductive fluoride and a conductive assistant.

[0033] The fluoride ion conductive fluoride is not particularly limited as long as it has fluoride ion conductivity. For example, CeBaF x and BaLaF y Examples of fluoride ion conductive fluorides include Ce. 0.95 Ba 0.05 F 2.95 YaBa 0.6 La 0.4 F 2.4By including these fluoride ion conductive fluorides in the negative electrode for a fluoride ion secondary battery according to this embodiment, the fluoride ion conductivity can be improved.

[0034] The average particle size of the fluoride ion conductive fluoride is preferably in the range of 0.1 μm to 100 μm. If the average particle size of the fluoride ion conductive fluoride is within this range, a thin-layer electrode can be formed while having relatively high ion conductivity. The average particle size of the fluoride ion conductive fluoride is more preferably in the range of 0.1 μm to 10 μm.

[0035] The conductive assistant may be any one having electronic conductivity and is not particularly limited. For example, carbon black or the like is used as the conductive assistant. As the carbon black, furnace black, ketjen black, acetylene black, or the like can be used. By including these conductive assistants in the negative electrode for a fluoride ion secondary battery according to this embodiment, the electronic conductivity can be improved.

[0036] The average particle size of the conductive assistant is preferably in the range of 20 nm to 50 nm. If the average particle size of the conductive assistant is within this range, an electrode having high electronic conductivity can be formed with a small weight.

[0037] Moreover, the negative electrode of the fluoride ion secondary battery according to this embodiment may contain other components such as a binder, within a range that does not impair the effects of this embodiment.

[0038] Next, a method for producing a negative electrode for a fluoride ion secondary battery according to this embodiment will be described in detail with reference to FIGS. Here, Fig. 4 is a diagram showing an example of a method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment. Fig. 5 is a diagram showing an example of a conventional method for producing a negative electrode for a fluoride ion secondary battery. The production method shown in Fig. 5 is a method for producing a modified AlF 2 O 4 obtained by doping lithium metal into conventional aluminum fluoride, which has already been proposed by the present applicant. 3This shows a manufacturing method of the above.

[0039] In one example of the manufacturing method of this embodiment shown in FIG. 4, first, CeBaF as a solid electrolyte made of a fluoride ion conductive fluoride is prepared. x (Ce 0.95 Ba 0.05 F 2.95 ) and 50 mg of carbon black (acetylene black AB) as a conductive additive are mixed.

[0040] Next, the mixture was treated with Li 3 AlF 6 and AlF 3 After adding 250 mg of the composite, for example, 300 rpm, 15 minutes, 40 cycles of ball milling are performed. This results in a composite LiAlFCB for the negative electrode for a fluoride ion secondary battery according to the present embodiment. The resulting composite LiAlFCB is then pressed together with a negative electrode current collector such as gold foil at a predetermined pressure to be integrated, thereby producing the negative electrode for a fluoride ion secondary battery according to the present embodiment.

[0041] In addition, Li 3 AlF 6 and AlF 3 The mixture ratio of the complex and the fluoride ion conductive fluoride can be selected arbitrarily. However, as described above, the Li 3 AlF 6 and AlF 3 The content of the complex is preferably 25% by mass or less, and from the viewpoint of increasing the charge capacity, the higher the ratio of the fluoride ion-conductive fluoride, which is the fluorine source, the more preferable.

[0042] In addition, as is clear from a comparison between the method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment shown in FIG. 4 and the method for producing a negative electrode for a fluoride ion secondary battery according to the related art shown in FIG. 5, the difference between the two production methods is that the negative electrode active material added to the mixture of the fluoride ion conductive fluoride and the conductive assistant is different. In the method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment, Li synthesized by the above-mentioned synthesis method is used as the negative electrode active material. 3 AlF 6 and AlF 3 By adding the complex, fluoride ion conductive fluoride, conductive additive, and Li 3 AlF 6 and AlF 3 In addition, the negative electrode mixture for a fluoride ion secondary battery is obtained by doping lithium metal into aluminum fluoride, which is added in the conventional method for producing a negative electrode for a fluoride ion secondary battery. 3 Details of the synthesis method etc. are as described in PCT / JP2019 / 039886.

[0043] Incidentally, in the negative electrode for a fluoride ion secondary battery according to the present embodiment produced by the production method shown in FIG. 4, Li 3 AlF 6 and AlF 3 Since the composite is unstable, the crystal structure is destroyed and made amorphous by the ball mill treatment. 3 AlF 6 and AlF 3 Even if the composite is subjected to X-ray diffraction measurement, no peak can be confirmed. Therefore, an NMR measurement can be used as an alternative measurement method to the X-ray diffraction measurement. According to this NMR measurement, the Li 3 AlF 6 and AlF 3 It is possible to detect a complex of

[0044] FIG. 6 shows a Li 3 AlF 6 and AlF3 More specifically, FIG. 6 shows the NMR spectrum of the Li complex synthesized according to the synthesis method shown in FIG. 3 AlF 6 and AlF 3 The solid-state NMR spectrum of the complex is shown in Fig. 1. The NMR measurement conditions are as follows:

[0045] (NMR measurement conditions) NMR device: “JNM-ECA600” manufactured by JEOL Probe: Agilent 1.6 mm triple resonance MAS probe Temperature: room temperature Spin condition: 35kHz Reference material: 7 Li is LiCl, 19 F is CFCl 3 , 27 Al is Al(NO 3 ) 3

[0046] As shown in Figure 6, Li 3 AlF 6 and AlF 3 In the NMR spectrum of the complex, a large peak is observed at a chemical shift of 180 ppm. This large peak is due to Li 3 AlF 6 Characteristic of 19 The peak is attributed to AlF. A large peak is also observed at a chemical shift of 170 ppm. This large peak is due to AlF 3 Characteristic of 19 The peaks are assigned to F. Therefore, the Li 3 AlF 6 and AlF 3 It is understood that the presence or absence of the complex can be confirmed by solid-state NMR measurement.

[0047] According to the negative electrode for a fluoride ion secondary battery according to the present embodiment described above, the following effects are achieved.

[0048] In the negative electrode for a fluoride ion secondary battery according to this embodiment, Li is used as the negative electrode active material. 3 AlF 6 and AlF 3 The composition includes a complex of Li 3 AlF 6 and AlF 3 The complex is Li 3 AlF 6 and AlF 3 is a composite material within a single particle, and has ionic conductivity. 3 AlF 6 However, it functions as a fluorine source and also acts as a defluorinator for AlF, which is normally difficult to defluorinate. 3 In addition, as mentioned above, Li 3 AlF 6 and AlF 3 The composite is a modified AlF 3 It can be made denser than Li and has high ionic conductivity. 3 AlF 6 and AlF 3 The composite is a conventional modified AlF 3 The concentration can be increased compared to Li, which can increase the battery capacity. 3 AlF 6 and AlF 3 In the composite of the above, even if the concentration is increased, an increase in the volume can be suppressed. Therefore, the content of the solid electrolyte made of the fluoride ion-conductive fluoride and the content of the conductive additive can be increased, resulting in a higher ion conductivity and a further increase in the battery capacity.

[0049] In addition, the negative electrode for a fluoride ion secondary battery according to this embodiment can obtain a high active material utilization rate in the first charge / discharge cycle, and can also obtain a high coulombic efficiency. 3 In the Li-ion battery of this embodiment, the active material utilization rate is low at about 40% and the Coulomb efficiency is also low at about 50%. 3 AlF 6 and AlF 3According to this composite, a high active material utilization rate of about 70% can be obtained, and a high Coulombic efficiency of about 80% can also be obtained.

[0050] [Fluoride ion secondary battery] The fluoride ion secondary battery according to this embodiment includes the above-mentioned negative electrode for fluoride ion secondary batteries. The fluoride ion secondary battery according to this embodiment also includes a solid electrolyte layer made of a solid electrolyte having fluoride ion conductivity, and a positive electrode.

[0051] As the solid electrolyte constituting the solid electrolyte layer, a conventionally known solid electrolyte can be used. Specifically, the same fluoride ion-conducting fluoride as described above can be used.

[0052] As the positive electrode, a conventionally known positive electrode active material is used, and it is preferable to use a positive electrode that can obtain a sufficiently high standard electrode potential compared to the standard electrode potential of the negative electrode for the fluoride ion secondary battery according to this embodiment. In addition, by selecting a material that does not have fluoride ions as the positive electrode, a battery that can be started by charging can be realized. In other words, it becomes possible to manufacture a battery in a discharge state where the energy state is low, and the stability of the active material in the electrode can be improved.

[0053] Specific examples of the positive electrode material include Pb, Cu, Sn, Bi, Ag, etc., conductive additives, binders, etc. For example, a positive electrode can be manufactured by pressing a positive electrode mixture containing lead fluoride, tin fluoride, carbon black, etc. together with a positive electrode material and a lead foil or the like as a current collector at a predetermined pressure to integrate them.

[0054] Therefore, the fluoride ion secondary battery according to the present embodiment can be manufactured by sequentially stacking the negative electrode for the fluoride ion secondary battery according to the present embodiment, the solid electrolyte layer, and the positive electrode. The fluoride ion secondary battery according to the present embodiment exhibits the same effects as the negative electrode for the fluoride ion secondary battery according to the present embodiment.

[0055] The present invention is not limited to the above-described embodiment, and the present invention includes modifications and improvements within the scope that can achieve the object of the present invention. For example, in the above embodiment, the present invention is described as being applied to a solid-state battery, but is not limited thereto, and may be applied to a fluoride ion secondary battery that uses an electrolytic solution instead of a solid electrolyte layer. EXAMPLES

[0056] Next, examples of the present invention will be described, but the present invention is not limited to these examples.

[0057] [Examples 1 and 2] According to the method for producing the negative electrode for a fluoride ion secondary battery according to the present embodiment shown in FIG. 4, the negative electrodes for a fluoride ion secondary battery according to Examples 1 and 2 were produced. In both Examples 1 and 2, Li 3 AlF 6 and AlF 3 The composite was made of the above, a fluoride ion conductive fluoride having an average particle size of 0.1 to 100 μm, and a conductive assistant having an average particle size of 20 to 50 nm. 3 AlF 6 and AlF 3 The content of the composite was set to 25 mass %. 3 The molar ratio of LiF:AlF 3 = 1:1 as Li 3 AlF 6 and AlF 3 In Example 2, a composite of LiF and AlF was synthesized. 3 The molar ratio of LiF:AlF 3 = 2:1 as Li 3 AlF 6 and AlF 3 The complex was synthesized.

[0058] [Comparative Example 1] According to the conventional method for producing a negative electrode for a fluoride ion secondary battery shown in FIG. 5 and the synthesis method described in PCT / JP2019 / 039886, a negative electrode for a fluoride ion secondary battery according to Comparative Example 1 was produced. In Comparative Example 1, a modified AlF 3 Modified AlF in the negative electrode for fluoride ion secondary batteries 3 The content was set to 25 mass %.

[0059] [Reference example 1] According to the method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment shown in FIG. Reference example 1 We have produced a negative electrode for a fluoride ion secondary battery using LiF and AlF 3 The molar ratio of LiF:AlF 3 =3:1, the average particle size of Li is on the order of micrometers (10μm~100μm). 3 AlF 6 A negative electrode for a fluoride ion secondary battery using a fluoride ion conductive fluoride having an average particle size of 0.1 to 100 μm and a conductive assistant having an average particle size of 20 to 50 nm was used as Reference Example 1. 3 AlF 6 The content was set to 25 mass %.

[0060] [Charge / discharge test] A half cell was prepared using the negative electrode for a fluoride ion secondary battery prepared in each Example, and a constant current charge / discharge test was carried out. Specifically, a potentiogalvanostat device (Sotron, SI1287 / 1255B) was used to carry out a constant current charge / discharge test under a vacuum environment of 140°C, with a charge current of 0.04 mA and a discharge current of 0.02 mA, a lower limit voltage of -2.44 V, and an upper limit voltage of -0.1 V.

[0061] Each half cell was prepared as a cylindrical pellet-type cell by pressing at a pressure of 40 MPa using a tablet press. Specifically, each half cell was prepared by putting gold foil (99.99%, thickness 10 μm) manufactured by Nilaco Corporation as a negative electrode current collector, 10 mg of the negative electrode composite powder for fluoride ion secondary batteries prepared in each Example, 200 mg of solid electrolyte, 30 mg of positive electrode composite powder, and lead foil (99.99%, thickness 200 μm) manufactured by Nilaco Corporation as a positive electrode material and positive electrode current collector in this order into a tablet press.

[0062] [Results / Discussion] Fig. 7 is a diagram showing charge / discharge curves of the negative electrode half cells for fluoride ion secondary batteries according to Examples 1 and 2, Reference Example 1, and Comparative Example 1. More specifically, Fig. 7 shows charge / discharge curves in the first charge / discharge cycle in Examples 1 and 2, Reference Example 1, and Comparative Example 1. As shown in Fig. 7, the modified AlF 3 In Comparative Example 1, in which the content of Li was 25 mass %, almost no charge / discharge capacity was obtained. 3 AlF 6 and AlF 3 In Examples 1 and 2, in which the content of the composite is 25 mass%, Li 3 AlF 6 It was confirmed that a large charge / discharge capacity equivalent to that of Reference Example 1 containing 25 mass % of Li as the negative electrode active material was obtained. From this result, it was confirmed that the present example can obtain a large charge / discharge capacity equivalent to that of Reference Example 1 containing 25 mass % of Li as the negative electrode active material. 3 AlF 6 and AlF 3 It was confirmed that the content of the composite could be increased up to 25 mass %, resulting in a battery capacity greater than that of conventional batteries.

[0063] In addition, the capacity that can actually be obtained is expressed by the utilization rate of the active material compared to the theoretical capacity. 3 AlF 6 and AlF 3The theoretical capacity of the composite is 2.48mAh, and from the results in Fig. 7, the charge capacity in Examples 1 and 2 is about 1.7mAh, and it was confirmed that a high active material utilization rate of about 68% was obtained according to this example. Furthermore, from the results in Fig. 7, it was confirmed that, according to Example 1, a discharge capacity of about 1.3mAh was obtained for a charge capacity of about 1.7mAh, and a high Coulombic efficiency of about 80% was obtained.

Claims

1. A negative electrode for a fluoride ion secondary battery comprising a negative electrode active material, The negative electrode active material is Li 3 AlF 6 and AlF 3 The complex includes The composite of Li 3 AlF 6 and AlF 3 is amorphous, and the molar ratio of AlF 3 to Li 3 AlF 6 is 0.1 to 2.

2. The Li in the negative electrode for the fluoride ion secondary battery 3 AlF 6 and AlF 3 2. The negative electrode for a fluoride ion secondary battery according to claim 1, wherein the content of the complex is 25 mass % or less.

3. A fluoride ion secondary battery comprising the negative electrode for a fluoride ion secondary battery according to claim 1 or 2.

Citation Information

Patent Citations

  • Amorphous body of lithium fluoroaluminate

    JP1982082820A

  • Fluoride ion battery

    JP2017050113A

  • Fluoride ion all solid state battery

    JP2018092863A

  • Fluoride ion battery

    JP2018198130A

  • Positive electrode active material and fluoride ion battery

    JP2018206755A